Significant clinical worsening after natalizumab withdrawal: Predictive factors. (May 2015) - Vidal-Jordana, A; Tintoré, M; Tur, C; Pérez-Miralles, F; Auger, C; Río, J; Nos, C; Arrambide, G; Comabella, M; Galán, I; Castilló, J; Sastre-Garriga, J; et al.
We aimed to single out multiple sclerosis (MS) cases with poor outcome after natalizumab withdrawal and to identify predictive variables. We ascertained 47 withdrawals, and compared their pre- and post-natalizumab periods. We objectively defined significant clinical worsening after natalizumab withdrawal as a 2-step increase in Expanded Disability Status Scale (EDSS). We performed regression models. As a group, post-natalizumab annualized relapse rate (ARR) was lower in the post-natalizumab period, and there were no differences in the mean number of gadolinium (Gd)-enhancing lesions between pre- and post-natalizumab magnetic resonance imaging (MRI). Corticosteroid treatment did not change the outcomes. Eight patients (19%) presented significant clinical worsening after natalizumab withdrawal, which was predicted by a higher baseline EDSS and a 1-step EDSS increase while on natalizumab.